Pengenalan penggunaan teknologi kedirgantaraan drone untuk meningkatkan mutu siswa SMK Muhammadiyah Sentolo dalam bidang agroindustri - Hariyanto, Kris; Poerwanto, Eko (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2023)
Sentolo Muhammadiyah Vocational School is located in the Kulon Progo area, more precisely on Sentolo-Magelang, Ngeplang, Sentolo, Kulon Progo roads. His areas of expertise are Motorcycle Business Engineering (TBSM), Automotive Light Vehicle Engineering (TKRO), Computer Network Engineering (TKJ). SMK Muhammadiyah Sentolo continues to carry out the process to improve and develop itself. One of them is by creating a Plus Program with the aim of preparing graduates who have resilience and independence. One of the plus programs is agroindustry Therefore, it is necessary to introduce agricultural processing methods using technology, especially technology that supports the fertilization process using liquid fertilizer. This Community Service Activity will introduce the use of fertilization technology using liquid media with the help of drones. The result of this service activity is that students know that the use of drones to help the fertilization process is meaningful for farmers, so students feel eager and enthusiastic to learn how to use the drone. On the farmer's side, they feel that the presence of drones applied by SMK Muhamaadiyah Sentolo students is a new hope that will be useful for helping farmers